SODIUM CONTENT PROFILE OF PACKAGED PROCESSED FOODS AND ITS COMPLIANCE WITH WHO GLOBAL SODIUM BENCHMARKS - Risda Yulianti; Okdi Natan; Vina Dwinata (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Packaged processed foods have become an integral part of modern lifestyles, yet they often contain high sodium levels that pose significant risks for hypertension and cardiovascular diseases. This study aims to evaluate the sodium content of packaged processed foods in Bengkulu City based on the 2nd Edition of the WHO Global Sodium Benchmarks. A descriptive cross-sectional study was conducted in May 2024, analyzing 500 products across 22 food subcategories sourced from modern retail outlets. Data on sodium content were collected from nutrition facts labels and converted to mg/100 g or mg/100 ml to ensure comparability with international standards. The results revealed that the highest median sodium levels were found in concentrated bouillon (3,914 mg/100 g), soy sauce (2,000 mg/100 ml), and instant noodles (1,294 mg/100 g). A vast majority of products, particularly canned fish (0% compliance), savory nut and seed snacks (0% compliance), and instant noodles (2.63% compliance), failed to meet the WHO benchmarks. Conversely, subcategories such as soy sauce (100%) and chocolate (81.81%) demonstrated high compliance rates. In conclusion, most packaged foods in the local market significantly exceed international sodium standards. These findings underscore the urgent need for integrative national benchmarks and progressive food reformulation policies to mitigate the burden of non-communicable diseases in Indonesia.